ChemInform Abstract: Synthesis and Evaluation of Novel 4‐Substituted Styryl Quinazolines as Potential Antimicrobial Agents. Issue 16 (28th March 2013) - Modh, Rahul P.; Patel, Amit C.; Mahajan, Dharmesh H.; Pannecouque, Christophe; De Clercq, Erik; Chikhalia, Kishor H.
Abstract A series of novel styrylquinazoline derivatives incorporating urea (VII) or thiourea moieties (IX) (22 examples in all) are designed synthesized and evaluated for their anti‐HIV and antibacterial activities.